Kelayakan Usaha Perikanan Agrowisata Pemancingan Nila Anjani - Bahruddin Yusuf; Maria Ulfah Riani Riani (Faculty of Science and Technology University Ibrahimy, 2026)
The Nila Anjani Fishing Spot is located in Mentaos Village. Visitors are charged an entrance fee of IDR 50,000, providing full access to fish without time restrictions during operating hours, from 8:00 AM to 11:00 PM WITA. The uniqueness of this fishing spot is that visitors are not charged additional fees for fish caught. All fish caught are included in the ticket price, thus providing comfort and convenience for visitors. The purpose of this research at the Nila Anjani agrotourism fishing spot in Banjarbaru City, South Kalimantan is to analyze the benefits of the Nila Anjani agrotourism fishing spot and analyze the business feasibility and prospects of the Nila Anjani agrotourism fishing spot. The selection of this research location was chosen intentionally (purposive), because this fishing spot is different from those that have existed in Banjarbaru City, South Kalimantan Province. This research was conducted from February to March 2026. The total cost incurred by the Nila Anjani agrotourism fishing reached Rp 46,108,995 per year with an annual income of Rp 158,150,000 resulting in a profit of 112,041,005 per year. Business feasibility is seen from the R/C ratio value of 3.43 which indicates that every Rp 1 of costs incurred produces Rp 3.43 in income. The payback period is around 1.15 years indicating that the capital is returned in less than 1 year and 2 months. The BEP production is 922 visitors and the BEP price is 14,578 which is far from the number smaller than the number of visitors who come and the price of tickets sold per piece so that the Nila Anjani agrotourism fishing business is very profitable